Russia, route zone A : Murman Railway and Kola Peninsula : information and route notes Murmansk to Petrograd - United States. War Dept. Military Intelligence Division. Military Monograph Subsection. (Washington : G.P.O., 1918)
"This report contains information on this subject obtained by the Military Monograph Subsection to October 1918." Mode of access: Internet.